ANTHROPOCENE, DISABILITIES AND SOCIALVULNERABILITIES: MENTAL HEALTH PROBLEMSAND DEVELOPMENT OF CHILDREN WITHDISABILITIES - Silva Torres Matsushita, Luciana (LINKSCIENCEPLACE, 2025)
The Anthropocene and the climate emergency are making disasters like the one that oc-curred in Rio Grande do Sul increasingly frequent. This fact especially affects children in situations ofgreater social vulnerability, such as those historically marginalized by socioeconomic structures conso-lidated in the exploitation and degradation of nature and human life. The new environmental and publichealth challenges affect minorities most affected by intersectionalities established in the overlapping ofsocial markers of difference, such as gender, race, class and disabilities, as indicated by reports fromUNESCO and the World Bank. In addition to the presented issues, there are major challenges in theschooling of children and youth with disabilities, who suffer prejudice and discrimination commonly ex-pressed in different forms of ableism, whether explicit or veiled. Free play and access to nature are notalways guaranteed rights to children with disabilities. This fact can result in the compromise of the ove-rall development and mental health of children, due to barriers consolidated in the insecurities of familymembers, teachers and communities. The perception of disability and its interaction with the increasedrisk of violence in certain urban, rural and forest areas and of accidents due to the lack of accessibilityin public and private spaces, can constitute limiting factors for inclusion. In this dramatic scenario, thereis a need for active research, in which theory embraces reality based on formal and informal educationpractices and political activism in defense of children and the environment. As final considerations, it isworth noting that change needs to begin today so that the future of new generations is less challengingthan projections indicate.